CXCR3 Is Involved in Tubulointerstitial Injury in Human Glomerulonephritis - Segerer, Stephan (American Society for Investigative Pathology, 2004)
Chemokines play pivotal roles in the recruitment of inflammatory cells into the kidney. The chemokine receptors CXCR3 and CCR5 are expressed on activated T lymphocytes, and expression of CXCR3 by mesangial cells has been suggested. Detailed description of CXCR3 expression might form a rational basis for use as a diagnostic marker and for therapeutic CXCR3 targeting in human glomerulonephritis. We studied the expression of CXCR3 in renal biopsies by immunohistochemistry (n = 45), and real time RT-PCR (n = 78). Biopsies were from patients with IgA nephropathy, lupus nephritis, and membranoproliferative glomerulonephritis. Furthermore, cultured human mesangial cells (HMC) were studied for CXCR3 expression, and for functional responses to the ligands CXCL10/IP-10 and CXCL9/Mig. CXCR3-positive cells were rarely found in glomerular tufts, but formed a major part of the tubulointerstitial infiltrates. Consistently, CXCR3 mRNA expression was too low to be quantified in glomerular compartments, and was not detectable in HMC. The published staining for CXCR3 of mesangial cells could be traced to cross-reactivity of an antibody for CXCR3 with a potentially related chemokine receptor as revealed by FACS analysis. Despite an absence of CXCR3 expression, mesangial cells reacted to CXCR3 ligands by proliferation and migration, which was blocked by pertussis toxin but not by an anti-CXCR3 antibody. These results indicate that HMC do not express the classical CXCR3, but may potentially express a related receptor with shared ligand specificity. By immunohistochemistry the number of CXCR3-positive cells, mainly interstitial T cells, correlated with renal function, proteinuria, and percentage of globally sclerosed glomeruli. A significant morphological and numerical correlation between CD3, CXCR3, and CCR5-positive cells indicated a CXCR3/CCR5 double-positive T cell population. No apparent difference in the CXCR3 expression pattern was found between disease entities. CXCR3 expression was localized to interstitial T cells, and these cells correlated strongly with important prognostic markers. Therefore interstitial CXCR3, as well as CCR5-positive T cells might play an important role during progressive loss of renal function, and are potential therapeutic targets in human glomerular diseases.